2016
DOI: 10.1016/j.tate.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Teacher candidate performance assessments: Local scoring and implications for teacher preparation program improvement

Abstract: h i g h l i g h t sLocally-scored performance assessments partially-aligned with construct framework. Locally-scored performance assessments systematically higher than official scores. Locally-scored performance assessments significantly predict teacher outcomes. Candidate performance assessments may inform evidence-based program improvement. a b s t r a c tLocally-scored teacher candidate performance assessments offer teacher preparation programs (TPPs) formative performance data, common language and expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…Our policy is if states have the technical ability to match edTPA performance to student learning in practice we will support studies of predictive validity. We have been following a few published studies (using pilot, local evaluation or first year edTPA data in WA and NC) and these studies are cited in the 2015 and 2016 Administrative Reports (see Bastian, Henry, Pan, & Lys, 2015;SCALE, 2016SCALE, , 2017. We have also cited a preliminary study from Tennessee that demonstrated data associating edTPA performance and teacher evaluation ratings (by principals) combined with student achievement.…”
Section: Claim: Edtpa Measures More Than Teachingmentioning
confidence: 99%
“…Our policy is if states have the technical ability to match edTPA performance to student learning in practice we will support studies of predictive validity. We have been following a few published studies (using pilot, local evaluation or first year edTPA data in WA and NC) and these studies are cited in the 2015 and 2016 Administrative Reports (see Bastian, Henry, Pan, & Lys, 2015;SCALE, 2016SCALE, , 2017. We have also cited a preliminary study from Tennessee that demonstrated data associating edTPA performance and teacher evaluation ratings (by principals) combined with student achievement.…”
Section: Claim: Edtpa Measures More Than Teachingmentioning
confidence: 99%
“…Most of the teacher evaluation programs were based on students' achievement scores, and they provide no information about specific teaching practices teachers do, no information for teachers to identify the problems stem from programs, and provide no evidence for teacher performances (Bastian et al 2016;Henry et al 2010). Although recently, other measurement instruments such as classroom observations and questionnaires are advocated by the education researchers (Henry et al 2010), they all suffer from a problem; they come too late to help teachers improve (Bastian et al 2016). Student rating process does not show goal attainment, increase teacher effectiveness, and student learning (Hughes and Pate 2012).…”
Section: Developing a Measure For Teacher Competencesmentioning
confidence: 99%
“…Bastian et al (2016) compared locally and officially scored performance assessment, and the results of their study indicated that local scores were higher than official scores. However, to make high stake decisions, locally scored performance assessment is not appropriate.…”
Section: Developing a Measure For Teacher Competencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacity issues did not only relate to the technology and use of computer software to run analyses but also relate to the competences of educators to formulate research questions, isolate relevant data outputs, interpret results and effectively develop and use classroom assessments [25]. This is why, in recent years, public concern for the quality of teacher education is pushing accreditation agencies and policymakers to hold EPPs accountable for the effectiveness of their completers [27]. CAEP requires EPPs' self-studies to provide impact data for their completers working with K-12 students.…”
Section: Conditions In the Epps And K-12 School Districts Regarding Datmentioning
confidence: 99%